Serum High Sensitivity CRP (HsCRP) in Psoriasis - Vaishali Dhat; Sumit Murhe; Alka Sontakke (International Journal of Medical Research and Review, 2014)
Introduction: Psoriasis is a common and recurrent proliferative inflammatory skin disease that has been associated with abnormal plasma lipid metabolism and with high frequency of cardiovascular morbidity and mortality. Dyslipidemia in psoriatic patients make them more prone for CAD. Highly sensitive C reactive protein (HsCRP) is a recent and sensitive marker of the inflammation particularly in atherosclerotic changes. So the levels of hsCRP and lipid profile were evaluated in psoriatic patients.Material and Methods: The study included 35 psoriatic patients and 35 healthy age and sex matched controls. Both the groups were evaluated for serum lipid profile and HsCRP levels.Results: The study showed that there was a significant rise in the levels of hsCRP in patients of psoriasis as compared to the controls (p<0.001) These psoriatic patients were also significantly dyslipidemic as compared to the controls.Conclusion: The study showed that psoriatic patients are more prone for atherosclerotic changes and CAD. Raised hsCRP can be considered as an added risk factor in Psoriatic patients with regard to coronary artery diseases. Special attention thus should be given if diagnosed earlier for lifestyle modification and exercise in these patients to minimize the atherosclerotic changes. Role of antioxidant supplementation needs further studies in patients of psoriasis.